Achievement and Personality Pattern of Secondary Level Scheduled Tribe Students in Relation to Gender and Type of Institutions - Panda, B.N.; Behera, Laxmidhar (JOURNAL OF INDIAN EDUCATION, 2011)
Scheduled Tribes (STs) are one of the recognised disadvantaged groups of the country. The present paper is an outcome of a research conducted with an objective to study the achievement and personality pattern of Scheduled Tribe students of six tribal concentrated districts of Odisha. The study reveals that (1) the residential secondary school students score better than non residential students in aggregate achievement (2) the non government secondary school students perform better than government school students. The non government secondary school students are found to have higher level of mean academic achievement than government secondary school students. The study also reports that achievement doesn’t have significant relationship with the personality pattern as a whole. But achievement of total sample students has significant positive relationship with only two of the fourteen HSPQ (R.B.Cattel) factors, i.e. ‘less intelligent vs. more intelligent’ and ‘phlegmatic vs. excitable’. Based on the findings the study suggests some realistic measures for education of Scheduled Tribe Students of the country.